LAMPUNGESE PHATIC EXPRESSION - Reranta, Redika Cindra (Linguistik, Terjemahan, Sastra (LINGTERSA), 2022)
Lampungese is one of the endangered languages today as some researchers claim. Therefore, hard efforts are needed to be conducted such as documenting, maintaining, and revitalizing the language. This paper was done to document one of the language features in Lampungese called phatic. Phatic is an expression word that does not have a certain meaning lexically but has a function in communication socially and pragmatically. Abundant examples for this can be found easily in spoken Lampungese in Lampung province, often they are uttered too in Indonesian spoken by people in the province. The step taken was to gather necessary data in form of talks and interviews. The data collected were then classified into smaller groups based on each characteristic. Having the data classified, a comprehensive analysis was then done to be able to answer the research question. In doing the analysis, the researcher was assisted by some native speakers who measured the analysis correctly. The findings cover various forms and functions of phatic. The first, phatic in Lampungese are found in the form of particle, word, phrase, and combination of phatic. The second finding shows that phatic is used as an affirmation of invitation, an affirmation of predicate, affirmation imperatives, comment markers, evidentiary affirmations, and familiarity builders. Moreover, phatic in Lampungese also expresses a certain emotional condition of the speaker. Those findings enrich the reference of Lampungese especially and linguistics generally.